Prediction of conserved peptides containing multiple T and B cell epitopes in Ebola virus glycoprotein - Kapur, Shinjan (My University, 2015)
Glycoprotein (GP) is the surface protein of Ebola virus (EBOV), responsible for penetration of the virus into the host cell cytoplasm by mediating the fusion of the membrane of the endocytosed virus particle with the endosomal membrane. Hence EBOV GP is considered to be the main target for design of vaccine and entry inhibitors. Due to extreme pathogenicity of EBOV, a high degree of biohazard containment is required for laboratory studies and clinical analysis and thus the conventional approach of vaccine and therapeutic development is hampered. Thus a cost and time effective approach needs to be adopted. Present study uses an immunoinformatics approach to identify conserved peptides containing multiple T and B cell epitopes of GP protein in three virulent species Zaire ebolavirus, Sudan ebolavirus and Bundibugyo ebolavirus using sequences available till August 2014. Different prediction algorithms have been used for peptide containing multiple epitopes and four conserved peptides were identified containing multiple epitopes for both T and B cells. The fragment LRQLANETTQALQLFLRATTELRTFSILNRKAIDFLL, out of the final four peptide fragments, contained maximum number of predicted epitopes for CD8+ and CD4+ cells. After studying the crystal structure of GP protein, it was found that this peptide lies in the heptad repeat regions HR1 and HR2 of GP2. Population coverage analysis has shown that all four peptides have the capacity to induce immune response among the different populations of the world and they are found to have binding affinity to large number of HLA alleles. Molecular docking studies revealed that all four peptides have comparable binding energy with that of the native peptide. Thus these peptides can further be evaluated for their potency as vaccine development against Ebola hemorrhagic fever.
M.Tech-Biotechnology
Keywords: Immunoinformatics; Ebola Virus; T cell Epitope; Vaccine; HLA; biotechnology; btes